Perfluoropolyether-terminated single-ion polymer, preparation method and application thereof, and battery comprising single-ion polymer
By blending the perfluoropolyether-capped single-ion polymer with PEO, the problem of easy decomposition of PEO-based electrolyte under high pressure and insufficient dendrite suppression ability of negative electrodes is solved, and the high cycle stability and rate performance of lithium metal batteries are achieved .
Patent Information
- Application Number
- CN202411306214.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-11
AI Technical Summary
PEO-based solid electrolyte is easy to decompose under high pressure, and its negative dendrite suppression ability of lithium metal batteries is insufficient, resulting in poor circulation stability.
Perfluoropolyether-terminated single-ion polymers are used to blend them with PEO, and the lithium ion migration number and window voltage are increased through polymer design, and the electrolyte reaction is delayed by forming a stable SEI layer.
It significantly improves the cycle stability and rate performance of PEO-based lithium metal batteries, extends the cycle life of the battery and improves the electrochemical window.
Smart Images

Figure BDA0005049282300000031 
Figure BDA0005049282300000032 
Figure BDA0005049282300000033
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer electrolytes, and in particular to a perfluoropolyether-terminated single-ion polymer, a preparation method and application thereof, and a battery comprising the single-ion polymer. Background Art
[0002] Polymers play an increasingly important role in our daily lives. Polymer electrolytes are a specific application of polymers. Nowadays, in the pursuit of high energy density and lightweight batteries, polymer electrolytes are gaining more and more attention from researchers due to their low cost, low density and strong plasticity. In particular, research on the preparation of functional polymers for electrolytes and flexible wearable devices is becoming increasingly popular.
[0003] Solid-state batteries refer to batteries with no liquid inside and inorganic or organic polymer solids as the battery electrolyte. Solid-state electrolytes have been sought after by researchers because of their high energy density, good safety performance, and long cycle life. In 1973, Fenton et al. proposed the coordination effect between alkali metals and polyethylene oxide (PEO), providing a theoretical basis for solid-state electrolytes. Lithium metal solid-state batteries are regarded as the next generation of batteries because of their high theoretical specific capacity.
[0004] Therefore, there is an urgent need to improve the performance of solid polymer electrolytes in lithium metal solid-state batteries.
[0005] The matrices used in polymer electrolytes mainly include polyethylene oxide (PEO), polyester, polyacrylonitrile and polyvinylidene fluoride. PEO is favored by researchers because of its excellent compatibility with lithium salts, good mechanical properties and low cost. The PEO / LiX system is a typical solid polymer system, in which the PEO chain coils around the lithium ions to separate the lithium ions from the X-counter anions. Generally, the transport of lithium ions is considered to be the movement of lithium ions between complexing sites, which is assisted by the segmented movement of the PEO polymer matrix, such as Figure 1 Specifically, Li + Ions tend to localize at coordination sites in polar polymer chains (e.g. -O- in PEO), which undergo constant local segmental motion, thus creating free volume for ion transport. +Ions migrate between coordination sites along polymer chains or hop in free bodies. The performance of lithium metal batteries has been improved with the development of solid-state electrolytes. Generally, electrolytes prepared by directly mixing PEO with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) exhibit low lithium ion migration numbers and limited electrochemical windows. During cycling, lithium dendrites tend to grow on the negative electrode, which has a significant impact on the cycle life of the battery. Single-ion conductors refer to a class of lithium salts in which anions are fixed to a polymer matrix through chemical reactions. It significantly reduces the mobility of anions and increases the migration number of lithium ions. In addition, constructing a solid electrolyte interface (SEI) layer on the anode can delay further reactions between the anode and the electrolyte, delay dendrite deposition, and enhance battery stability. Therefore, the performance of PEO-based solid polymer electrolytes can be significantly improved by adopting single-ion conductors and constructing SEI layer strategies.
[0006] However, the following key issues remain unresolved in the preparation of high-performance PEO-based electrolytes: (1) PEO-based electrolytes are not resistant to high voltages and will decompose at 3.8 V. (2) PEO-based electrolytes have a weak ability to inhibit negative electrode dendrites. Summary of the invention
[0007] In view of the low lithium ion migration number, low window voltage, and poor cycle stability of PEO-based solid electrolytes, the present application provides a perfluoropolyether-terminated single-ion polymer, a preparation method and application thereof, and a battery including the single-ion polymer. The present application adopts a scheme of synthesizing a new polymer, focusing on the PEO-based electrolyte window voltage, lithium ion migration number, and the problem of inhibiting the growth of dendrites at the negative electrode of PEO-based electrolyte lithium metal batteries. The polymer is blended with PEO through polymer design to improve the performance of PEO-based lithium metal batteries.
[0008] The present application utilizes the advantage of perfluoropolyether being preferentially reduced at the negative electrode to form a stable SEI layer and delay further reaction of the electrolyte under the electric field, thereby increasing its window voltage. At the same time, the single ion part in the polymer fixes the anion on the polymer skeleton, thereby increasing the lithium ion migration number of the electrolyte and alleviating the uneven deposition and structural deterioration of the electrode during repeated dissolution / deposition, thereby obtaining a solid electrolyte material with excellent cycle stability and rate performance.
[0009] This application can not only provide a new design idea for the research of solid electrolyte materials for lithium metal batteries, but also provide necessary technical support and theoretical support for exploring the development of polyether polymer electrolytes, which has important academic significance and practical value.
[0010] In the first aspect, the present application provides a perfluoropolyether terminated single ion polymer, using the following technical solution:
[0011] A perfluoropolyether-terminated monoionic polymer having the following structural formula (1):
[0012]
[0013] The number average molecular weight of the monoionic polymer is 14500-18000 g / moL;
[0014] x:y=(1-2):(2-1).
[0015] Optionally, the number average molecular weight of the monoionic polymer is 15000-16500 g / moL.
[0016] Optionally, the number average molecular weight of the single ion polymer is 15210 g / moL.
[0017] Optionally, x:y=13:25.
[0018] In the second aspect, the present application provides a macromolecular initiator, which adopts the following technical solution:
[0019] A macromolecular initiator has the following structural formula (2):
[0020]
[0021] In a third aspect, the present application provides a method for preparing the above-mentioned macromolecular initiator, using the following technical scheme:
[0022] A method for preparing a macromolecular initiator, the synthetic route is as follows:
[0023]
[0024] The macroinitiator was prepared by the esterification reaction of α-bromoisobutyryl bromide with PFPE-OH catalyzed by triethylamine and 4-(dimethylamino)pyridine.
[0025] In a fourth aspect, the present application provides a method for preparing the above-mentioned perfluoropolyether-terminated single-ion polymer, using the following technical scheme:
[0026] A method for preparing a perfluoropolyether-terminated monoionic polymer, wherein the above-mentioned macromolecular initiator is used in the preparation method.
[0027] Alternatively, the synthetic route is as follows:
[0028]
[0029] Optionally, the macromolecular initiator, tris(2-dimethylaminoethyl)amine, lithium bis(trifluoromethanesulfonyl imide), polyethylene glycol monomethyl ether acrylate, CuBr2 and copper foil are added to a reaction bottle, dissolved in a mixed solvent of DMSO and trifluorotoluene, degassed with argon, and reacted at 60-80°C for 40-56h.
[0030] In a fifth aspect, the present application provides the use of the above-mentioned single-ion polymer as a polymer electrolyte to enhance the performance of PEO electrolyte in a battery.
[0031] In a sixth aspect, the present application provides a single-ion polymer membrane, which comprises the above-mentioned single-ion polymer.
[0032] In a seventh aspect, the present application provides a battery comprising the above-mentioned single-ion polymer membrane.
[0033] In summary, the present application includes at least one of the following beneficial technical effects:
[0034] This application adopts a scheme of synthesizing a new polymer, focusing on the PEO-based electrolyte window voltage, lithium ion migration number and the problem of inhibiting the growth of negative electrode dendrites of PEO-based electrolyte lithium metal batteries. The polymer is blended with PEO through polymer design to achieve the purpose of improving the performance of PEO-based lithium metal batteries.
[0035] The present application utilizes the advantage of perfluoropolyether being preferentially reduced at the negative electrode to form a stable SEI layer and delay further reaction of the electrolyte under the electric field, thereby increasing its window voltage. At the same time, the single ion part in the polymer fixes the anion on the polymer skeleton, thereby increasing the lithium ion migration number of the electrolyte and alleviating the uneven deposition and structural deterioration of the electrode during repeated dissolution / deposition, thereby obtaining a solid electrolyte material with excellent cycle stability and rate performance.
[0036] Assemble steel sheet||steel sheet, steel sheet||lithium sheet, lithium sheet||lithium sheet CR2016 coin battery for electrochemical test. PFPE-SE sample has 1.31×10 -4 The room temperature ionic conductivity is 4.7 S / cm, the electrochemical window is 4.7V, and the lithium ion transference number is 0.72.
[0037] Constant current charge and discharge tests were carried out on a NEWARE battery tester to obtain the cycle performance of the samples. The PFPE-SE sample maintained good cycle stability and high specific capacity. The assembled Li||LFP battery obtained 146.7 mAh g at a current density of 0.2C. -1 The capacity retention rate after 220 cycles is greater than 75.9%. The assembled Li||LFP battery obtained 156.0mAh·g at a current density of 0.5C. -1The specific capacity of the sample is greater than 74.3% after 230 cycles. These indicate that the sample has great potential and advantages in obtaining a solid electrolyte material with good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the mechanism of lithium ion transport in PEO.
[0039] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of PFPE-initiator.
[0040] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of PFPE-polymer.
[0041] Figure 4 These are digital photos and SEM electron microscope photos of PFPE-SE.
[0042] Figure 5 This is the impedance curve of PFPE-SE steel sheet||steel sheet (steel sheet / electrolyte / steel sheet) battery at different temperatures.
[0043] Figure 6 This is the test result of lithium ion migration number of PFPE-SE at 70℃.
[0044] Figure 7 The window voltage test results of PFPE-SE at 70℃.
[0045] Figure 8 Symmetric lithium battery of PFPE-SE at 0.1 mAh cm -2 @0.1mA cm -2 Dissolution / deposition under
[0046] Fig. 9 The comparison results of the cycling performance of PFPE-SE and PEO-SE at 0.2C.
[0047] Fig.10 The comparison results of the cycling performance of PFPE-SE and PEO-SE at 0.5C.
[0048] Fig.11 The comparison results of rate performance between PFPE-SE and PEO-SE. DETAILED DESCRIPTION
[0049] Before describing the embodiments of the present application in detail, it should be understood that the terms used herein are only used for the purpose of describing specific embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by ordinary technicians in the field to which the terms belong.
[0050] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0051] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0052] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0053] The present application provides a perfluoropolyether-terminated monoionic polymer having the following structural formula (1):
[0054]
[0055] The number average molecular weight of the monoionic polymer is 14500-18000 g / moL;
[0056] x:y=13:25.
[0057] In a specific embodiment, the number average molecular weight of the monoionic polymer is 15210 g / mol, and x:y=13:25.
[0058] The present application also provides a method for preparing the above-mentioned single ion polymer. The macromolecular initiator, tris(2-dimethylaminoethyl)amine, lithium bis(trifluoromethanesulfonyl imide), polyethylene glycol monomethyl ether acrylate, CuBr 2 and copper foil are added to a reaction bottle, dissolved in a mixed solvent of DMSO and trifluorotoluene, degassed with argon, and reacted at 60-80°C for 40-56h.
[0059] The present application also provides the use of the above-mentioned single-ion polymer as a polymer electrolyte to improve the performance of PEO electrolyte in a battery.
[0060] Specifically, the application may be a single-ion polymer membrane, which comprises the above-mentioned single-ion polymer.
[0061] Specifically, the application may be a battery comprising the above-mentioned single-ion polymer membrane.
[0062] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0063] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0064] The present application is further described in detail below in conjunction with the embodiments, drawings and test results.
[0065] Example
[0066] Example 1
[0067] This embodiment provides a perfluoropolyether-terminated macroinitiator PFPE-initiator. The synthesis process of the macroinitiator is as follows:
[0068]
[0069] By triethylamine (ET 3 The macroinitiator PFPE-initiator was prepared by the acyl bromide esterification reaction of α-bromoisobutyryl bromide (BIBB) with PFPE-OH catalyzed by N) and 4-(dimethylamino)pyridine (4-DMAP).
[0070] At 0°C, a solution of BIBB (0.345 g, 1.50 mmol) in trifluorotoluene (TFT, 5 mL) was added dropwise to PFPE-OH (1.0 g, 1.0 mmol), ET 3 N (0.303 g, 3 mmol) and 4-DMAP (0.019 g, 0.16 mmol) in trifluorotoluene (10 mL) were added. After the addition, the reaction mixture was stirred at room temperature for 20 h.
[0071] The reaction mixture was washed twice with 1M sodium hydroxide solution and then washed twice with distilled water. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated in vacuo, and precipitated in methanol to remove unreacted BIBB and by-products. The desired component was concentrated in vacuo to obtain a brown oil product (0.8 g, 0.67 mmoL, yield 80%), which was the macromolecular initiator PFPE-initiator.
[0072] PFPE-initiator H NMR spectrum Figure 2 As shown, the results are as follows: 1 H NMR (500 MHz, deuterated chloroform) δ 4.78-4.63 (m, 2H), 1.93 (s, 6H).
[0073] Example 2
[0074] This embodiment provides a perfluoropolyether-terminated single-ion polymer PFPE-polymer. The synthesis process of the single-ion polymer is as follows:
[0075]
[0076] The macromolecular initiator PFPE-initiator (400 mg, 0.4 mmoL, 1 equivalent) prepared in Example 1, tris(2-dimethylaminoethyl)amine (Me 6 TREN, 16.56 mg, 0.072 mmoL, 0.18 equivalents), lithium bis(trifluoromethanesulfonyl)imide (LiSTFSI, 2.5 g, 8 mmoL, 20 equivalents), polyethylene glycol monomethyl ether acrylate (1.9 g, 3 mmoL, 7.5 equivalents), CuBr 2 (9 mg, 0.04 mmoL, 0.1 equivalent) and a small piece of copper foil were added to the reaction bottle, dissolved in 10 mL of a mixed solvent (DMSO and trifluorotoluene, volume ratio of 1:1), degassed with argon, and then reacted at 70 °C for 48 h.
[0077] The reaction vessel was opened, methanol was added and mixed thoroughly, and then the mixture was placed in a dialysis bag with a molecular weight cutoff of 1000 Da, sealed and placed in a flowing methanol solution for dialysis. After two days of dialysis, the dialysis bag was opened to concentrate the remaining solvent to obtain the product, which is a single-ion polymer PFPE-polymer.
[0078] The H NMR spectrum of PFPE-polymer is as follows: Figure 3 The results are as follows: The H NMR spectrum showed that the polymer was successfully synthesized, and the molecular weight was 15,210 Da as calculated by the H NMR spectrum. The H NMR spectrum showed that one initiator polymerized 25 LiSTFSIs and 13 acrylate monomers, with x:y = 13:25.
[0079] Example 3
[0080] This embodiment provides a perfluoropolyether-terminated single-ion polymer-modified PEO electrolyte (PFPE-SE). The synthesis process of the single-ion polymer-modified PEO electrolyte is as follows:
[0081] A solid electrolyte with an average thickness of 150 μm was prepared by conventional solvent casting. Specifically, 300 mg of the single-ion polymer PFPE-polymer prepared in Example 2, 500 mg of polyethylene oxide (PEO) and 50 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in acetonitrile, heated and vigorously stirred for 6 h to form a uniform mixed solution; the mixture was then poured into a mold, the solvent was dried, and a thin film was formed, which was a single-ion polymer modified PEO electrolyte. Among them, the salt concentration of PFPE-SE (i.e. [-CH 2 CH 2 O-(EO)] / [Li + ] ratio) were maintained at a molar ratio of 16:1.
[0082] Digital photos and SEM electron microscope photos of PFPE-SE are shown in the figure below. Figure 4 As shown,
[0083] Performance test 1
[0084] The battery was assembled using the single ion polymer modified PEO electrolyte PFPE-SE prepared in Example 3, and the following electrochemical tests were performed. The details are as follows:
[0085] (1) Impedance curves at different temperatures
[0086] The detection method is as follows: use 2016 battery shells to test these button batteries in an argon atmosphere (O 2 ≤0.01ppm, H 2 O≤0.01ppm) and sealed. The battery was left at 70°C for 5 h before ionic conductivity measurement. The ESI curve of the electrochemical workstation is obtained by the formula Calculated.
[0087] Test results such as Figure 5 shown.
[0088] Depend on Figure 5 It can be seen that at 70°C, the conductivity of PFPE-SE is 1.31×10 -4 S / m.
[0089] (2) Lithium ion migration number
[0090] The detection method is as follows: The lithium ion migration number is obtained by chronoamperometry and electrochemical impedance spectroscopy (EIS). The prepared Li0|SEs|Li0 battery is subjected to constant potential polarization test at an applied voltage of 10 mV. The lithium ion migration number is calculated according to the Bruce-Vincent-Evans equation.
[0091] Test results such as Figure 6shown.
[0092] Depend on Figure 6 It can be seen that the lithium ion transference number of PFPE-SE reaches 0.72 at 70°C.
[0093] (3) Window voltage
[0094] The detection method is as follows: Linear voltammetry (LSV) measurements were recorded on an electrochemical workstation. The electrochemical stability measurements were performed in the voltage range of 0 V to 6 V at a scan rate of 0.01 mV / s.
[0095] Test results such as Figure 7 shown.
[0096] Depend on Figure 7 It can be seen that the PFPE-SE window voltage reaches 4.7 V at 70°C.
[0097] (4) 0.1 mAh cm -2 @0.1mA cm -2 Dissolution / deposition under
[0098] The detection method is as follows: the lithium deposition-stripping measurement method, the polymer electrolyte is sandwiched between two lithium foils to make a button cell. The button cell is in an argon atmosphere (O 2 ≤0.01ppm, H 2 O≤0.01ppm) and sealed. The battery was left at 70°C for 5 h before further testing. The Li0||Li0 symmetric battery was stripped and deposited on a NEWARE cycle test system with a current density of 0.1 mA cm -2 .
[0099] Test results such as Figure 8 shown.
[0100] Depend on Figure 8 It can be seen that tests have shown that the PEO electrolyte doped with PFPE-polymer has a cycle time of up to 550 hours and exhibits excellent stability.
[0101] Comparative Example
[0102] This comparative example provides a PEO electrolyte (PEO-SE). The synthesis process of the PEO electrolyte is as follows:
[0103] 500 mg PEO and 200 mg LiTFSI were dissolved in 10 ml acetonitrile, stirred vigorously at 60° C., and then poured into a polytetrafluoroethylene mold and dried to prepare an electrolyte film.
[0104] Performance test 2
[0105] The following electrochemical tests were performed on a battery assembled with the single-ion polymer modified PEO electrolyte PFPE-SE prepared in Example 3, and compared with the test results of a battery assembled with the PEO-SE prepared in the comparative example. The details are as follows:
[0106] (1) Cycling performance at 0.2C
[0107] The detection method is as follows: a polymer electrolyte is sandwiched between a lithium foil and a positive electrode material to form a button battery. The button battery is placed in an argon atmosphere (O 2 ≤0.01ppm, H 2 O≤0.01ppm) and sealed. The battery was left at 70°C for 5h before further testing. The Li|SEs|LFP battery was subjected to charge and discharge cycle tests on a NEWARE cycle test system, and the cycle performance test was performed at a rate of 0.2C.
[0108] Test results such as Fig. 9 shown.
[0109] Depend on Fig. 9 It can be seen that the Li||LFP battery assembled using the single-particle polymer-modified PEO electrolyte PFPE-SE provided in this application can obtain 146.7 mAh g at a current density of 0.2C. -1 The specific capacity of the Li||LFP battery assembled with PEO-SE provided in the comparative example obtained 150.56 mAh g at a current density of 0.2C. -1 The specific capacity of the battery failed after only 90 cycles, and the capacity retention rate was 72% at the 90th cycle.
[0110] (2) Cycling performance at 0.5C
[0111] The detection method is as follows: a polymer electrolyte is sandwiched between a lithium foil and a positive electrode material to form a button battery. The button battery is placed in an argon atmosphere (O 2 ≤0.01ppm, H 2 O≤0.01ppm) and sealed. The battery was left at 70°C for 5h before further testing. The Li|SEs|LFP battery was subjected to charge and discharge cycle tests on a NEWARE cycle test system, and the cycle performance test was performed at a rate of 0.5C.
[0112] Test results such as Fig.10 shown.
[0113] Depend on Fig.10It can be seen that the Li||LFP battery assembled using the single-particle polymer-modified PEO electrolyte PFPE-SE provided in this application obtains 156.0 mAh·g at a current density of 0.5C. -1 The specific capacity of the Li||LFP battery assembled with PEO-SE provided in the comparative example obtained 157.3 mAh g at a current density of 0.5 C. -1 The specific capacity of the battery failed after only 66 cycles, and the capacity retention rate was 89% at the 66th cycle.
[0114] (3) Rate performance
[0115] The detection method is as follows:
[0116] The polymer electrolyte is sandwiched between lithium foil and positive electrode material to make a button battery. The button battery is in an argon atmosphere (O 2 ≤0.01ppm, H 2 O≤0.01ppm) and sealed. The battery was left at 70°C for 5h before further testing. The Li|SEs|LFP battery was subjected to charge and discharge cycle tests on a NEWARE cycle test system, and the cycle performance was tested at a rate of 0.1C-1.0C.
[0117] Test results such as Fig.11 shown.
[0118] Depend on Fig.11 It can be seen that at a current density of 0.6C, the PFPE-SE electrolyte enables the battery to maintain 147.25 mAh g -1 The specific capacity of PEO-SE was only 85.27 mAh g -1 At a current density of 1C, the PFPE-SE electrolyte enables the battery to maintain a specific capacity of 114.4 mAh g -1 The specific capacity of PEO-SE was only 34.6 mAh g -1 The specific capacity of PFPE-polymer-doped PEO electrolyte has better high current density tolerance.
[0119] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A perfluoropolyether terminated monoionic polymer, characterized in that: It has the following structural formula (1): The number average molecular weight of the monoionic polymer is 14500-18000 g / moL; x:y=(1-2):(2-1).
2. The monoionic polymer according to claim 1, characterized in that The number average molecular weight of the monoionic polymer is 15000-16500 g / moL; Optionally, the number average molecular weight of the monoionic polymer is 15210 g / moL; Optionally, x:y=13:
25.
3. A macromolecular initiator, characterized in that It has the following structural formula (2):
4. A method for preparing the macromolecular initiator according to claim 3, characterized in that: The synthetic route is as follows: The macroinitiator was prepared by the esterification reaction of α-bromoisobutyryl bromide with PFPE-OH catalyzed by triethylamine and 4-(dimethylamino)pyridine.
5. A method for preparing a perfluoropolyether-terminated monoionic polymer according to any one of claims 1 to 2, characterized in that: The preparation method uses the macromolecular initiator described in claim 3.
6. The preparation method according to claim 5, characterized in that: The synthetic route is as follows:
7. The preparation method according to claim 5, characterized in that: The macromolecular initiator, tris(2-dimethylaminoethyl)amine, lithium bis(trifluoromethanesulfonyl)imide, polyethylene glycol monomethyl ether acrylate, CuBr2 and copper foil are added to a reaction bottle, dissolved in a mixed solvent of DMSO and trifluorotoluene, degassed with argon, and reacted at 60-80°C for 40-56h.
8. Use of the single-ion polymer according to any one of claims 1 to 2 as a polymer electrolyte to improve the performance of PEO electrolyte in a battery.
9. A single ion polymer membrane, characterized in that The single-ion polymer membrane comprises the single-ion polymer according to any one of claims 1-2.
10. A battery, characterized in that: The battery comprises the single-ion polymer membrane of claim 9.
Citation Information
Cited By
Lithium ion battery diaphragm with dual-function coating and preparation method of lithium ion battery diaphragm
CN122026002A
A lithium ion battery separator with a dual functional coating and a method of making the same
CN122026002B